2020
DOI: 10.3390/ijerph17020565
|View full text |Cite
|
Sign up to set email alerts
|

Readmissions to General ICUs in a Geographic Area of Poland Are Seemingly Associated with Better Outcomes

Abstract: Background: Various factors can contribute to high mortality rates in intensive care units (ICUs). Here, we intended to define a population of patients readmitted to general ICUs in Poland and to identify independent predictors of ICU readmission. Methods: Data derived from adult ICU admissions from the Silesian region of Poland were analyzed. First-time ICU readmissions (≤30 days from ICU discharge after index admissions) were compared with first-time ICU admissions. Pre-admission and admission variables that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Recently, Weigl et al, 49 after analyzing the national Polish ICU outcome database, reported a high observed ICU mortality of 43.5%. Grochla et al 50 hypothesized an explanation that the absence of clear futile therapy legislation, the unpopularity of advanced directives, the insufficiency of rapid response team implementation, the fear of legal consequences in cases of refusing ICU admission, the extreme pressure on ICU admissions due to the poor development of intermediate care, and the lack of funding for patients with a lower TISS-28 score (< 19 pts.) are responsible for this high mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Weigl et al, 49 after analyzing the national Polish ICU outcome database, reported a high observed ICU mortality of 43.5%. Grochla et al 50 hypothesized an explanation that the absence of clear futile therapy legislation, the unpopularity of advanced directives, the insufficiency of rapid response team implementation, the fear of legal consequences in cases of refusing ICU admission, the extreme pressure on ICU admissions due to the poor development of intermediate care, and the lack of funding for patients with a lower TISS-28 score (< 19 pts.) are responsible for this high mortality rate.…”
Section: Discussionmentioning
confidence: 99%